Evaluation of Information Technology Governance by Using CobIT 5 Framework at Higher Education - Jonhariono Sihotang; Erwin Setiawan Panjaitan; Roni Yunis (Jurnal Mantik, 2020)
IT (Information Technology) governance is an important thing in every organization where at this time Information Technology has become an important role in the sustainability of an organization. Therefore, to produce good organizational goals, good IT governance is needed as well. In this study, there are several problems that must be managed by the organization but have been summarized in the problem of resource optimization. To solve these problems, the COBIT 5 framework was chosen as a framework that would become a reference for solving these problems. There are 16 processes that will solve organizational problems, namely EDM02, EDM04, APO01, APO03, APO04, APO07, APO08, APO10, APO13, BAI01, BAI02, BAI04, DSS01, DSS03, DSS04, MEA01 and using PAM (Process Assessment Model) as tools to evaluate. The purpose of this study was to determine the level of organizational IT capabilities, and to analyze the gap between the organizational target value (to be) and the capability value obtained by the current organization (to be). After knowing the gap value, this value will be used as a basis for producing a recommendation for improvement for the organization.